Métodos y técnicas en la enseñanza y su aporte en el aprendizaje significativo en el área de ciencias naturales en los estudiantes de la Unidad Educativa Luz de América cantón Montalvo, Provincia Los Ríos - Icaza Sobenis, Coralia Mónica (2019)
The subject of Natural Sciences is of great importance, since it is essential to understand the world around us, hence its importance in education. However, it has been shown that the educational process of teaching - learning has been affected by the traditional, which has been negative in school performance. The present work is directed, a development of the abilities and skills for the resolution of problems of the daily reality, by means of the use of interactive techniques. Constitute a relevant tool that will support the teaching-learning process of this subject, because the teacher will improve the school environment by enhancing learning. The light of America Canton Montalvo, Province of Los Ríos. For what, an organization of activities has been developed, a field study has been carried out to know the current situation of the problem, the surveys have been carried out, the interviews directed to the experts, the teaching staff, it has been said that they are part of the institution, the sample It was not intentional probabilistic. Where the leaders will be the students, the teachers and the authorities of the establishment and those who contribute to fulfill the aspiration of forming responsible people with the environment.